2019
DOI: 10.24156/jikk.2019.12.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi tentang Usia Pernikahan Perempuan dan Jumlah Anak yang Diharapkan: Mampukah Memprediksi Praktek Pengasuhan Orang Tua?

Abstract: Di Indonesia, usia ideal menikah dan jumlah anak ideal telah menjadi isu dalam pembangunan keluarga. Penelitian ini bertujuan untuk menganalisis persepsi usia pernikahan perempuan dan keinginan jumah anak pada keluarga dengan anak usia prasekolah di Indonesia dan kemudian dikaitkan dengan praktek pengasuhan yang dilakukan. Data yang digunakan dalam penelitian adalah data sekunder dari Survei Indikator Kinerja Program Kependudukan, Keluarga Berencana dan Pembangunan Keluarga (KKBPK) Rencana Pembangunan Jangka M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The causes of this phenomenon include economic difficulties, low education, coercion from parents, due to accidents, and due to the customs of the local community. Early marriage has an impact on biological and psychological aspects (Oktriyanto et al, 2019) This study is in line with the results of research conducted by Vika Nurhaliza, Iroma Maulida and Nora Rahmanindar entitled "Adolescent Girls' Knowledge of the Impact of Early Marriage". In this study, it was found that the respondents had good knowledge of 71 young women (91%).…”
Section: B Overview Of Young Women's Knowledge About Preparation For ...supporting
confidence: 87%
See 1 more Smart Citation
“…The causes of this phenomenon include economic difficulties, low education, coercion from parents, due to accidents, and due to the customs of the local community. Early marriage has an impact on biological and psychological aspects (Oktriyanto et al, 2019) This study is in line with the results of research conducted by Vika Nurhaliza, Iroma Maulida and Nora Rahmanindar entitled "Adolescent Girls' Knowledge of the Impact of Early Marriage". In this study, it was found that the respondents had good knowledge of 71 young women (91%).…”
Section: B Overview Of Young Women's Knowledge About Preparation For ...supporting
confidence: 87%
“…One of the positive perceptions is attitudes towards premarital fertility, knowledge of contraceptives, and knowledge of sexual diseases. This perception is able to realize family programs, health, and influence policies and life in the family (Oktriyanto et al, 2019) .…”
Section: Introductionmentioning
confidence: 99%
“…Pengembangan kemampuan dasar anak sangat dipengaruhi oleh pola asuh orang tua atau keluarga yang dilakukan kepada anaknya, misalnya peraturan dan cara mendidik yang ketat sehingga anak merasa terkekang (Soetjiningsih, 1995).Penelitian menemukan bahwa praktek pengasuhan ibu yang negatif berupa pemberian ancaman dan hukuman untuk menghentikan perilaku anak yang tidak baik memengaruhi perilaku agresif pada anak usia prasekolah (Oktriyanto et al, 2019). Praktek pengasuhan yang negatif dapat meningkatkan perilaku negatif pada anak usia dini dikarena nkan anak mengikuti perilaku model yang diamatinya.…”
Section: Pendahuluanunclassified
“…16 of 2019 concerning changes to the Marriage Law article 7 paragraph (1) states that marriage is only permitted if a man or woman has reached the age of 19 (Ilma, 2020). Meanwhile, according to the National Population and Family Planning Agency (BKKBN) in 2017 the ideal age for marriage recommended by the government is 21 years for women and 25 years for men (Oktriyanto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%